School-to-school collaboration : learning across international contexts - Armstrong, Paul; Brown, Chris (Emerald Publishing Limited, 2022)
This collection of chapters from established thinkers and emerging scholars provides a series of unique insights into collaboration between schools and the means by which the policy context influences such activity. Taking a global perspective, the chapters within this book follow a common framework to explore how macro-level factors help to create the conditions in which school-to-school collaboration is likely to succeed or fail 'on the ground'. The result is a nuanced and original analysis that explores why and how collaborative activity between schools is intrinsically linked to broader policy contexts. School collaboration and networking is a rapidly growing area of interest. This book will appeal to the increasing number of emerging scholars and established experts with an interest in this area and other related sub-fields including school effectiveness and improvement, critical policy studies and educational leadership and management. It will also be of interest to policymakers seeking to capitalise on the potential of collaboration between schools and to educational professionals seeking improvement through partnership and dialogue.
Keywords: Inter-school cooperation.; Education -- Educational Policy & Reform -- General.; Educational strategies & policy.; elektronické knihy; electronic books